Development of a framework for the use of recycled concrete aggregates in concrete in the Philippines - Cura, Aimee Rebekah M.; Defiño, Joanne Clarise F.; Diola, Ma. Brida Lea D. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The construction industry in the Philippines is steadily growing and becoming even more vital to the achievement of national and socio-economic goals in terms of employment, shelter, and infrastructure. Despite the numerous benefits that can be incurred from this, an increase in the number of construction works unfortunately leads to an increase in the amount of construction and demolition wastes (CDW). One method that has been gaining popularity overseas for minimizing CDW is the use of recycled concrete aggregates (RCA) in the production of recycled aggregate concrete (RAC) for structural and non-structural applications. Although multiple countries have incorporated the use of this material in their laws and regulations, the use of concrete wastes in the Philippines is limited to backfill, pavements, and disposal at landfills. In this study, the current perceptions of major stakeholders of the construction industry were analyzed to develop a recommended framework for the use of RCA in the Philippines. It was observed that environmental benefits and economic benefits were the highest-ranking factors that would influence the decisions of contractors and agencies to use RCA, whereas concrete manufacturers prioritize the perception of the general public or marketability of the product. Furthermore, a review of overseas practices, laws and regulations showed similarities to local studies that were adjusted in the development of the said framework.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete; Aggregates (Building materials); Building materials -- Standards